Depression, anxiety, and stress scale: Psychometric properties and affectivity prevalence - Martins, Bianca Gonzalez [UNESP] (2019)
Objective: To estimate psychometric properties of the Depression Anxiety and Stress Scale (DASS-21) among Brazilian university students and to compare the prevalence of depression, anxiety, and stress between men and women. Methods: The DASS-21‘s fit was evaluated by confirmatory factor analysis using the chi-square per degrees of freedom ratio (c2/df), Comparative Fit Index (CFI), Tucker-Lewis Index (TLI) and Root Mean Square Error of Approximation (RMSEA). A second-order hierarchical model was tested (Negative Affectivity). The prevalence of depression, anxiety, and stress was calculated and compared by sex. Results: Participants comprised 1,042 university students [aged 18 to 35 years (mean = 21.13; standard deviation = 2.81 years) 65.7% women]. The DASS-21‘s goodness of fit was adequate (c2/df = 5.83; CFI = 0.96; TLI = 0.97; RMSEA = 0.07). However, item 2 presented low factorial weight and was excluded (c2/df = 6.05; CFI = 0.98; TLI = 0.97; RMSEA = 0.07). The study verified that 4.7%, 1.7%, and 4.5% of students presented moderate to extremely severe scores of depression, anxiety, and stress, respectively. There was no significant difference between men and women in the prevalence of the emotional aspects assessed. Conclusion: The DASS-21 demonstrated adequate validity and reliability in a sample of university students. The prevalence of depression, anxiety, and stress did not differ significantly between men and women, which points to the need for an egalitarian view in the investigation of these emotional states.